An experimental model for the transplantation of fetal central nervous system cells to the injured spinal cord in rats - Barros Filho, Tarcísio Eloy Pessoa de; Oliveira, Reginaldo Perilo de; Tsanaclis, Ana Maria; Barros, Erika Meirelles Kalil Pessoa de; Cristante, Alexandre Fogaça; Palma, Ricardo Moreira; Santos, Cristian Vilela dos; Marcon, Raphael Martus (Revista do Hospital das Clínicas, 2002)
INTRODUCTION: Traumatic spinal cord injury is one of the most disabling conditions occurring in man and thus stimulates a strong interest in its histopathological, biochemical, and functional changes, primarily as we search for preventive and therapeutic methods. PURPOSE: To develop an experimental model for transplantation of cells from the fetal rat central nervous system to the site of an injured spinal cord of an adult rat in which the transplanted cells survive and become integrated. This experimental model will facilitate investigations of factors that promote regeneration and functional recovery after spinal cord trauma. MATERIAL AND METHODS: Fifteen adult Wistar rats underwent laminectomy, and an spinal cord lesion was made with microdissection. Fetal spinal cord tissue was then transplanted to the site of the injury. The rats were monitored over a 48-hour period, and then their vertebral column was completely removed for histological analysis. RESULTS: In 60% of transplanted rats, the fetal tissue at the injured site remained viable in the site of the lesion.